EXPLORING NETWORKED IDENTITY AND TRANSNATIONAL MOBILIZATION IN UKRAINE’S EUROMAIDAN PROTEST - Lokot, Tetyana; Boichak, Olga (AoIR Selected Papers of Internet Research, 2020)
Social media are a prominent space for diasporic mobilization and activism, opening new avenues for studying transnational communities living outside of their countries of origin. This study uses a hybrid methodological approach to consider how Ukrainians living in the United States engaged with homeland politics during the 2013-2014 Euromaidan protest and how their use of social media intervened in their transnational protest politics. This study contributes to the broader scholarship on studying transnational mediated protest participation by examining a case of diasporic mobilization of the Ukrainian community in the United States. Triangulating semantic mapping data from online diasporic communities on Facebook with in-depth interviews, we show how diaspora members engaged in the protest despite distance and how their activity and tactical decisions were mediated by social networks. We specifically examine how diasporic personal networks and networked technologies enmesh into a set of hybrid networked practices, circumscribing how Ukrainian Americans interpret political engagement and how they strategically use the affordances of social media for protest participation.